Changes in the Content of Biogenic Amines and Fatty Acids in High Pressure-Processed Carp Flesh (Cyprinus carpio) - KříŽek, Martin; Matějkoá, Kateřina; Dadáková, Eva; Špička, Jiří; Vácha, František; Vrchotová, NaděŽda (Journal of food protection, 2015)
Biogenic amine and fatty acid contents were determined in vacuum-packed fillets of common carp (Cyprinus carpio). Samples were pressure treated at 300 and 500 MPa and were stored at 3.5 and 12°C for up to 28 days (control, 0 MPa) and 70 days (pressure-treated). The content of eight biogenic amines (putrescine, cadaverine, spermidine, spermine, histamine, tyramine, tryptamine, and phenylethylamine) were determined. Putrescine and cadaverine were influenced by all factors (temperature, pressurization level, and time of storage). Tyramine content was the most sensitive indicator of the improper status of sample; levels exceeding 10 mg/kg indicated both the loss of meat freshness and temperature abuse, in spite of persisting good sensory indices. Neither storage temperature nor pressurization level had a statistically important effect on the contents of fatty acids. Only polyunsaturated fatty acids decreased slightly if the storage time exceeded 42 days.
Keywords: Food Handling; Carps; mastné kyseliny; biogenní aminy; Food Packaging; Seafood; manipulace s potravinami; Biogenic Amines; Vacuum; kapři; vakuum; obaly potravin; Animals; Food Analysis; Fatty Acids; zvířata; potrava z moře (živočišná); analýza potravin